Pattern of Hematological Diseases treated at Birat Medical College and Teaching Hospital - Sapkota, Sulav; Priyadarshini, Mona (Birat Journal of Health Sciences, 2022)
Introduction: Hematological diseases are increasing day to day in the eastern region of Nepal. There are very few centers providing treatment to hematological diseases patients in the eastern region of Nepal. Objectives: The aim of this study is to stratify the types of hematological diseases treated at Birat Medical College and Teaching Hospital along with their demographic and clinic-pathological features. Methodology: This descriptive cross-sectional study was conducted from 21 December 2020 to 20 July 2021 in the Department of Hemato-Oncology. All the clinically as well as laboratorically proven hematological disease patients receiving treatment during the study period were taken as study population. Hematological diseases are blood related diseases like anemia, blood cancers (like leukemia , lymphoma , multiple myeloma) ,hemolytic diseases , coagulation disease ,thrombocytopenia, etc. Data were entered and analyzed in Microsoft Excel version 2010 and IBM SPSS Statistics version 22 respectively. Result: There were a total of 48 cases who received treatment during the study duration. The mean age of the cases was 50 (range 2-92) years with female gender almost equal to male gender. About 29% cases were involved in tobacco/ smoking . Majority of the cases involved were leukemia (33%), lymphoma (21%) ,hemolytic disease(11%) and Immune thrombocytopenic purpura(11%) cancer.We have good clinical remission (61%) of the cases, majority of which were non malignant cases. Total 77% of the cases were alive, 4% were referred while 19 % of the cases expired during the study period, majority of which were acute leukemias. Conclusion:There is a rise of hematological cancer in eastern Nepal and hence there is a need for a comprehensive hematological center in the eastern region of Nepal.